Implementation of Excellent Private Ibtidaiyah Madrasah Programs in Rural Areas - Ahmad Gawdy Prananosa; Donni Pestalozi; M. Rusni Eka Putra (Institut Agama Islam Negeri (IAIN) Curup, 2021)
This study aims to determine the implementation of the flagship program of private madrasah ibtidaiyah in rural areas. Using a qualitative approach with phenomenological methods. It was held at Madrasah Ibtidaiyah Assidiq Giriyoso, Jayaloka District. The research subjects consisted of the Principal, the Board of Teachers, and the Foundation. Data collection technique; observation, interview, and documentation. The data analysis step uses an interactive model from Miles and Huberman. The results of the research show that the implementation of the madrasah flagship program is implemented well, namely: 1) the material is delivered according to the ability level of the students, 2) the material delivered has been planned in the learning implementation plan, 3) the teacher is prepared to focus on the abilities of each student, so that the material what is conveyed can be easily accepted by students, 4) facilities and infrastructure, especially tahfiz boarding schools are prepared in front of their respective classes, 5) the curriculum prepared is in accordance with the analysis of students' abilities, which are listed in the learning implementation plan, 6) finances, especially in giving honorarium for teaching staff, according to the number of working hours that have been carried out, and 7) relations with the community are always well established, especially in supporting madrasah flagship programs, because the community is an important element in using products from madrasah. In conclusion, the implementation of the flagship program of tahfiz al-qur'an and English can really have a positive impact on the development of madrasah, because the alumni of madrasah ibtidaiyah Giriyoso are able to compete academically with other students, at the state junior high school level, so that parents entrust their children to school in madrasah